2019
DOI: 10.3390/su11030565
|View full text |Cite
|
Sign up to set email alerts
|

Designing with Pathways: A Spatial Design Approach for Adaptive and Sustainable Landscapes

Abstract: Despite rising attention to pathways thinking in multiple domains such as climate adaptation, energy supply planning, and flood risk management, their spatial translation is so far understudied. We set out to study how spatial design based on pathways thinking can help develop more adaptive and sustainable landscapes. Using landscape analysis, field research, and research-through-designing in a case study on climate resilience in Boston (USA), we argue for better understanding of the spatial and design consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Additionally, as there is growing attention in research to better understand hazard interactions ( Zscheischler et al., 2020 ; Poljansek et al., 2021 ), the proposed framework to create (intermediate-) adaptive pathways for single- or multi-hazard-related planning can already serve as useful information for sectoral users. This is expected to support the understanding of different sectoral stakeholders for multi-risk and to increase their willingness to participate in the process ( Butler et al., 2020 ; Zandvoort et al., 2019 ; Head, 2019 ). On the other hand, the integration of cross-sectoral knowledge might cause additional challenges owing to confidentiality requirements and lack of trust across sectors ( Scolobig et al., 2017 ) which complicates integrating knowledge and complexity.…”
Section: The Dapp-mr Frameworkmentioning
confidence: 96%
“…Additionally, as there is growing attention in research to better understand hazard interactions ( Zscheischler et al., 2020 ; Poljansek et al., 2021 ), the proposed framework to create (intermediate-) adaptive pathways for single- or multi-hazard-related planning can already serve as useful information for sectoral users. This is expected to support the understanding of different sectoral stakeholders for multi-risk and to increase their willingness to participate in the process ( Butler et al., 2020 ; Zandvoort et al., 2019 ; Head, 2019 ). On the other hand, the integration of cross-sectoral knowledge might cause additional challenges owing to confidentiality requirements and lack of trust across sectors ( Scolobig et al., 2017 ) which complicates integrating knowledge and complexity.…”
Section: The Dapp-mr Frameworkmentioning
confidence: 96%
“…(2014) examined in more details some of the challenges and implementation barriers for evacuation in an environmental-justice community, Kirshen et al. (2018) addressed how to involve vulnerable exposed populations in urban adaptation strategy planning and the use of multistakeholder collaborative processes, and Zandvoort et al. (2019) studied how pathway thinking can be used to inform landscape architects to design sustainable and adaptive landscapes.…”
Section: Case Studymentioning
confidence: 99%
“…This research is the fifth paper of a series of articles on climate change adaptation in Boston. Douglas et al (2012) identified major obstacles and incentives for adaptation based upon representative focus groups, Kuhl et al (2014) examined in more details some of the challenges and implementation barriers for evacuation in an environmental-justice community, addressed how to involve vulnerable exposed populations in urban adaptation strategy planning and the use of multistakeholder collaborative processes, and Zandvoort et al (2019) studied how pathway thinking can be used to inform landscape architects to design sustainable and adaptive landscapes.…”
Section: Case Studymentioning
confidence: 99%
“…1). Dams, dikes, and sea walls are hard infrastructure measures to keep water away from the cities which are grouped as hard engineering infrastructure as mentioned in literature (Vitale et al, 2020;Zandvoort et al, 2019). Accommodating measures support safety by offering building adjustments and retreat from the risk area.…”
Section: Design Strategies In Flood Risk Management Literaturementioning
confidence: 99%